Identifying distinctive psychological symptom profiles among a nationally representative sample of refugees resettled in Australia. (September 2019) - Nickerson, Angela; Hadzi-Pavlovic, Dusan; Edwards, Ben; O'Donnell, Meaghan; Creamer, Mark; Felmingham, Kim L; Forbes, David; McFarlane, Alexander C; Silove, Derrick; Steel, Zachary; van Hoof, Miranda; Bryant, Richard A
Objective: The number of refugees worldwide is unprecedented in recent history. Little is known, however, about profiles of psychological symptoms following persecution and displacement. Methods: This study reports on a latent class analysis that identified profiles of posttraumatic stress disorder (PTSD), depression and anxiety symptoms in a nationally representative sample of 1625 refugees in Australia. The association between specific symptom profiles, exposure to potentially traumatic events and post-migration stressors, and overall health and help-seeking was examined. Results: Latent class analysis yielded an optimal five-class solution. These classes comprised the Pervasive Symptom class (19.2%), the High PTSD Symptom class (17.1%), the High Depression/Anxiety Symptom class (16.4%), the Moderate PTSD Symptom class (16.2%) and the Low Symptom class (31.1%). Participants in the symptomatic classes were more likely to be female, older and report greater post-migration stressors than those in the Low Symptom class. In addition, individuals in classes characterized by PTSD symptoms had been exposed to more types of potentially traumatic events. Membership in symptomatic classes was associated with poorer overall heath and greater help-seeking. Conclusion: Qualitatively distinct symptom profiles were observed in a nationally representative sample of refugees. In addition to a group of people who reported high symptoms across psychological disorders and may warrant clinical intervention, we identified two subclinical classes who may be missed by existing diagnostic classification systems. Post-migration stressors play an important role in influencing refugee symptom profiles over and above exposure to potentially traumatic events. Clinicians should consider specific symptom profiles and contextual factors when planning interventions with refugees.